PENGARUH PENGETAHUAN PASIEN DAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN PENGOBATAN TUBERKULOSIS: TINJAUAN SISTEMATIS - NAILA APRILIYANI; SARI, NINA PAMELA (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Tuberculosis continues to be a major global health concern, with Indonesia being one ofthe countries with a high burden of cases. Patient adherence to treatment plays a crucialrole in preventing disease transmission, reducing mortality rates, and avoiding drugresistance. However, many patients do not follow treatment guidelines, whichcomplicates tuberculosis control efforts. Poor treatment adherence is often influenced byvarious factors, including patients’ knowledge of tuberculosis, family support, andsocioeconomic conditions. Limited understanding of the importance of regular treatmentand inadequate family support may worsen patients’ conditions and reduce the likelihoodof successful treatment outcomes. This study aims to examine the factors influencingtreatment adherence among tuberculosis patients, with a particular focus on the role ofpatient knowledge and family support. A systematic review methodology was employedby analyzing articles published between 2021 and 2024, retrieved from PubMed, GoogleScholar, and ScienceDirect. The literature search followed the PRISMA framework toidentify relevant studies. Among the four articles included in this review, good patientknowledge and strong family support were found to have a significant influence ontuberculosis treatment adherence. Patients with better understanding of tuberculosistreatment and strong family support tended to be more adherent to therapy, therebyreducing the risk of drug resistance and improving treatment success rates.Key Words: Tuberculosis, Treatment, Adherence, Family Support.